CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Biological soil amendments can support survival of pathogenic and non-pathogenic Escherichia coli in soils and sporadic transfer to Romaine lettuce - Zirui Ray Xiong; Ellen Gabriel; Alan Gutierrez; Cheryl East; Kalmia E. Kniel; Michelle D. Danyluk; Michele Jay-Russell; Manan Sharma (International Journal of Food Microbiology, 2025)

Trends in Arctic-nesting loon (Gavia spp.) populations in North America - Ingrid L. Pollet; Sarah E. Gutowsky; Ray T. Alisauskas; William Harvey; Dana K. Kellett; Kristen M. Lalla; Josée Lefebvre; Jake Russell-Mercier; Jennifer F. Provencher; Emily D. Silverman; Paul A. Smith; Mark L. Mallory (Polar Biology, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A review of iron species for visible-light photocatalytic water purification - Russell S. Jack; Godwin A. Ayoko; Moses O. Adebajo; Ray L. Frost (Environmental Science and Pollution Research, 2015)

Introduction to Special Issue of Bulletin of Volcanology on “Advances in Kimberlite Geology and Volcanology” - Ray Cas; J. K. Russell; R. Stephen J. Sparks (Bulletin of Volcanology, 2011)

Leaf isoprene emission rate as a function of atmospheric CO 2 concentration - MICHAEL J. WILKINSON; RUSSELL K. MONSON; NICOLE TRAHAN; STANFIELD LEE; ERIN BROWN; ROBERT B. JACKSON; H. WAYNE POLLEY; PHILIP A. FAY; RAY FALL (Global Change Biology, 2009)
There is considerable interest in modeling isoprene emissions from terrestrial vegetation, because these emissions exert a principal control over the oxidative capacity of the troposphere. We used a unique field experiment that employs a continuous gradient in CO 2 concentration from 240 to 520 ppmv to demonstrate that isoprene emissions in Eucalyptus globulus were enhanced at the lowest CO 2 concentration, which was similar to the estimated CO 2 concentrations during the last Glacial Maximum, compared with 380 ppmv, the current CO 2 concentration. Leaves of Liquidambar styraciflua did not show an increase in isoprene emission at the lowest CO 2 concentration. However, isoprene emission rates from both species were lower for trees grown at 520 ppmv CO 2 compared with trees grown at 380 ppmv CO 2 . When grown in environmentally controlled chambers, trees of Populus deltoides and Populus tremuloides exhibited a 30–40% reduction in isoprene emission rate when grown at 800 ppmv CO 2 , compared with 400 ppmv CO 2 . P. tremuloides exhibited a 33% reduction when grown at 1200 ppmv CO 2 , compared with 600 ppmv CO 2 . We used current models of leaf isoprene emission to demonstrate that significant errors occur if the CO 2 inhibition of isoprene is not taken into account. In order to alleviate these errors, we present a new model of isoprene emission that describes its response to changes in atmospheric CO 2 concentration. The model logic is based on assumed competition between cytosolic and chloroplastic processes for pyruvate, one of the principal substrates of isoprene biosynthesis.

Fit-for-Purpose Method Development and Validation for Successful Biomarker Measurement - Jean W. Lee; Viswanath Devanarayan; Yu Chen Barrett; Russell Weiner; John Allinson; Scott Fountain; Stephen Keller; Ira Weinryb; Marie Green; Larry Duan; James A. Rogers; Robert Millham; et al. (Pharmaceutical Research, 2006)

Amino Acid Deamination by Ruminal Megasphaera elsdenii Strains - Jennifer L. Rychlik; Ray LaVera; James B. Russell (Current Microbiology, 2002)

Song rates of dark-eyed juncos do not increase when females are fertile - Russell C. Titus; C. Ray Chandler; Ellen D. Ketterson; Val Nolan, Jr. (Behavioral Ecology and Sociobiology, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)